Surprises in Theoretical Casimir Physics Quantum Forces in Inhomogeneous Media - Simpson, William M.R (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
Despite more than half a century of theoretical work, the Casimir effect is still not as fully understood as some suppose. In this treatise, the author uncovers new puzzles and paradoxes concerning this mysterious phenomenon. In particular, he clearly demonstrates that the most sophisticated theories fail when confronted with dielectrics in which the refractive index is not uniform but gradually changes.